Analisis Gangguan Cairan Elektrolit dan Hipovolemia pada Penyakit Demam Berdarah Dengue (DBD): (Literatur Review) - Hasna Sari Kusnandar; Elsa Devina Seftiani; Muhammad Fhaisal Nur Halim; Nazwa Rahma Putri; Rendi Rizki Priyanto; Tri Ayuni; Faiza Zahra Amelia; Zahra Arifah; Aura Rukmana; Amanda Saskia Raika Putri; Popi Sopiah (Pusat Riset dan Inovasi Nasional, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical countries, including Indonesia, due to its high incidence and risk of severe complications. One of the most critical complications is hypovolemia, which is closely associated with fluid and electrolyte imbalance caused by plasma leakage. This study aimed to analyze the relationship between fluid imbalance, electrolyte disturbances, and hypovolemia in patients with DHF using a narrative literature review approach. Data were collected from several scientific databases, including Google Scholar, PubMed, Semantic Scholar, and Crossref, covering publications from 2021 to 2025. A total of 894 articles were identified in the initial search, and 6 articles that met the inclusion criteria were further analyzed. The findings showed that increased capillary permeability plays a key role in plasma leakage, leading to decreased intravascular volume and hypovolemia. In addition, electrolyte imbalances, particularly hyponatremia and hypokalemia, were frequently reported and associated with disease severity. These conditions may contribute to serious complications such as shock and organ dysfunction if not properly managed. Therefore, early detection, careful monitoring of fluid balance, and appropriate clinical management are essential to prevent complications and improve patient outcomes.